Caffeine prevents d-galactose-induced cognitive deficits, oxidative stress, neuroinflammation and neurodegeneration in the adult rat brain. (November 2015) - Ullah, Faheem; Ali, Tahir; Ullah, Najeeb; Kim, Myeong Ok
Abstract: d -galactose has been considered a senescent model for age-related neurodegenerative disease. It induces oxidative stress which triggers memory impairment, neuroinflammation and neurodegeneration. Caffeine act as anti-oxidant and has been used in various model of neurodegenerative disease. Nevertheless, the effect of caffeine againstd -galactose aging murine model of age-related neurodegenerative disease elucidated. Here, we investigated the neuroprotective effect of caffeine againstd -galactose. We observed that chronic treatment of caffeine (3 mg/kg/day intraperitoneally (i.p) for 60 days) improved memory impairment and synaptic markers (Synaptophysin and PSD95) in thed -galactose treated rats. Chronic caffeine treatment reduced the oxidative stress via the reduction of 8-oxoguanine through immunofluorescence in thed -galactose-treated rats. Consequently caffeine treatment suppressed stress kinases p-JNK. Additionally, caffeine treatment significantly reduced thed -galactose-induced neuroinflammation through alleviation of COX-2, NOS-2, TNFα and IL-1β. Furthermore we also analyzed that caffeine reduced cytochrome C, Bax/Bcl2 ratio, caspase-9, caspase-3 and PARP-1 level. Moreover by evaluating the immunohistochemical results of Nissl and Fluro-Jade B staining showed that caffeine prevented the neurodegeneration in thed -galactose-treated rats. Our results showed that caffeine prevents thed -galactose-induced oxidative stress and consequently alleviated neuroinflammation and neurodegeneration; and synaptic dysfunction and memory impairment. Therefore, we could suggest that caffeine might be a dietary anti-oxidant agent and a good candidate for the age-related neurodegenerative disorders. Graphical abstract: Highlights: Caffeine (3 mg/kg, i.p. 60 days) improved memory in thed -galactose-treated rats. Caffeine treatment prevents oxidative stress in thed -galactose-treated rats. Caffeine treatment prevents various inflammatory mediators. Caffeine treatment prevents apoptosis and neurodegeneration.